2020
DOI: 10.1038/s41467-020-15023-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient strain modulation of 2D materials via polymer encapsulation

Abstract: Strain engineering is a promising method to manipulate the electronic and optical properties of two-dimensional (2D) materials. However, with weak van der Waals interaction, severe slippage between 2D material and substrate could dominate the bending or stretching processes, leading to inefficiency strain transfer. To overcome this limitation, we report a simple strain engineering method by encapsulating the monolayer 2D material in the flexible PVA substrate through spin-coating approach. The strong interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
274
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(284 citation statements)
references
References 47 publications
6
274
4
Order By: Relevance
“…T wo-dimensional (2D) semiconductors have attracted considerable attention as ultrathin channel materials for transistors [1][2][3][4][5] . Their atomically thin body and danglingbond free surface offer significant potential for ultimate transistor scaling (down to atomic thin-body thickness), which is essential for decreasing off-state power consumption and further extending Moore's Law 6 .…”
mentioning
confidence: 99%
“…T wo-dimensional (2D) semiconductors have attracted considerable attention as ultrathin channel materials for transistors [1][2][3][4][5] . Their atomically thin body and danglingbond free surface offer significant potential for ultimate transistor scaling (down to atomic thin-body thickness), which is essential for decreasing off-state power consumption and further extending Moore's Law 6 .…”
mentioning
confidence: 99%
“…[ 257 ] The lattice registry growth of ME2DMs on certain substrates always introduces strain or stress, which offers an effective way to manipulate their electronic properties. [ 258 ] This method is promising for non‐optimized bandgap modulation through strain engineering but with limited tunability. Theoretically, biaxial strains above 6% can transform β‐antimonene from indirect to direct bandgap semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…Another thicknessdependent study on exfoliated MoS2/SiO2 samples also confirmed that the best PF occurs for bilayer MoS2. [49] Li and co-workers [51] measured tunable bandgap in monolayer MoS2 that changes with uniaxial strain at a modulation rate of up to ~136 meV/%, thus we may expect an even larger Seebeck coefficient in deformed MoS2 as flexible thermoelectric applications. Besides MoS2, exfoliated 3L WSe2 on SiO2 shows a peak Seebeck coefficient of around 200 μV/K for electron conduction and around 250 μV/K for hole conduction at 300 K. [52] The maximum PF reaches 3.7 mW/m•K 2 for p-type WSe2 and about 3.2 mW/m•K 2 for n-type, corresponding to electrical conductivities of approximately 3 × 10 4 S/m and 1 × 10 4 S/m respectively.…”
Section: Thermoelectric Properties Of 2d Tmdcsmentioning
confidence: 90%